2014
DOI: 10.1007/s10753-014-9860-y
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Inflammation Are Differentially Affected by Atorvastatin, Pravastatin, Rosuvastatin, and Simvastatin on Lungs from Mice Exposed to Cigarette Smoke

Abstract: Our aim was to investigate the effects of four different statins on acute lung inflammation induced by cigarette smoke (CS). C57BL/6 male mice were divided into a control group (sham-smoked) and mice exposed to CS from 12 cigarettes/day for 5 days. Mice exposed to CS were grouped and treated with vehicle (i.p.), atorvastatin (10 mg/kg), pravastatin (10 mg/kg), rosuvastatin (5 mg/kg), or simvastatin (20 mg/kg). Treatment with statins differentially improved the pulmonary response when compared to the CS group. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 78 publications
0
30
1
Order By: Relevance
“…Statins including ATV, exert pleiotropic effects such as anti-inflammatory, antioxidant, and immunomodulatory effects via cholesterol lowering, regulation of immune cells, reduction of cytokine and chemokine production and scavenging the oxygen-derived free radicals (Ferreira et al, 2014). We previously showed the antioxidant, anti-fibrotic and anti-inflammatory effects of ATV on PQ-induced oxidative stress, pulmonary fibrosis and inflammation in rodent model, respectively (Malekinejad et al, 2013(Malekinejad et al, , 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Statins including ATV, exert pleiotropic effects such as anti-inflammatory, antioxidant, and immunomodulatory effects via cholesterol lowering, regulation of immune cells, reduction of cytokine and chemokine production and scavenging the oxygen-derived free radicals (Ferreira et al, 2014). We previously showed the antioxidant, anti-fibrotic and anti-inflammatory effects of ATV on PQ-induced oxidative stress, pulmonary fibrosis and inflammation in rodent model, respectively (Malekinejad et al, 2013(Malekinejad et al, , 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Our hypothetical explanation finds confirmation in 2 recent trials based on intravascular ultrasound imaging with 'virtual histology' [28,29]; both trials confirmed that aggressive lipid lowering with statins increases the content of calcium in the coronary plaque. Statins have long been shown not only to lower LDL cholesterol effectively, but also to reduce inflammation and stabilize atherosclerotic plaques and part of the effect may imply calcification of the plaque core [30,31]. On the other hand, there is also experimental evidence that statins may promote calcification of cardiac structures [32].…”
Section: Data Interpretationmentioning
confidence: 99%
“…Hadi et al (2013) reported that SIMV ameliorates myocardial ischemia/reperfusion injury (38). Ferreira et al (2014) found that treatment of mice with 20 mg/kg of SIMV improved the pulmonary damage caused by exposure to tobacco smoke when compared to control animals (26).…”
Section: Discussionmentioning
confidence: 99%
“…In this experiment, the dose of Cr(VI) to induce oxidative stress was based on a report by Goodarzi et al (25) and Ferreira et al (26). The selected dose of SIMV was as per Ozbakis-Dengiz et al (27) and Mohammadi et al (28).…”
Section: Animal Treatmentsmentioning
confidence: 99%